Effects of benzo[ a]pyrene exposure on a fish population resistant to the toxic effects of dioxin-like compounds - Nacci, Diane E; Kohan, Michael; Pelletier, Marguerite; George, Elizabeth (Aquatic toxicology, 2002)
Effects of a model polycyclic aromatic hydrocarbon (PAH) were compared in populations of the estuarine fish Fundulus heteroclitus indigenous to a reference site and one highly contaminated with polychlorinated biphenyls (PCBs) and other compounds. The fish population resident to the PCB-contaminated site is genetically resistant to those PCB congeners categorized as dioxin-like compounds (DLCs) that act through the aryl hydrocarbon receptor (AHR). In response to DLC exposures, these DLC-resistant fish showed poor inducibility for enzymes known to be regulated by the AHR pathway and important for the metabolism of xenobiotics including some PAHs that also act as AHR agonists. Therefore, a laboratory study using the model PAH, benzo[ a]pyrene (BaP), was conducted to evaluate how PAHs might affect these wild fish populations that differed in their inherent sensitivities to DLCs and in their tissue concentrations of contaminants. Following BaP treatment, the activities of two xenobiotic metabolizing enzymes and the concentrations of BaP-DNA adducts, as measured using the 32P-postlabeling method, were lower in the livers of DLC-resistant than reference fish. These results suggest that DLC-resistance could provide protection following chronic exposures to PAHs from the long-term consequences of DNA adduct formation, such as cancer. Alternatively, reduced metabolism and elimination of toxic or photo-activated PAHs could have acute consequences to the health and reproduction of these DLC-resistant fish and their progeny. These fish populations provide useful models to evaluate the potential costs and benefits of genetic adaptation in wildlife populations subject to anthropogenic stress.